2021
DOI: 10.1002/jcop.22685
|View full text |Cite
|
Sign up to set email alerts
|

Mental health and discrimination among migrants from Africa: An Italian cross‐sectional study

Abstract: This study aimed to assess depression, anxiety, posttraumatic stress disorder (PTSD) and discrimination in African migrants and investigate determinants. A cross-sectional study was conducted in Italy (July 2019-February 2020).Inclusion criteria: being a citizen of an African country or having parents who are citizens of an African country.Questionnaires included tests for depression, anxiety, PTSD, discrimination. Multivariable regressions were performed. Participants were 293. The prevalence of depression, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Indeed, the heterogeneous nature of the immigration phenomenon in Italy entails varied experiences of adjustment and integration across cultural communities. For instance, individuals who are characterized by distinct phenotypic traits (e.g., Chinese and African origins) or a larger cultural/religious distance from members of the mainstream society (e.g., Muslims) are at risk of being stigmatized and discriminated against (Ambrosini, 2013; Voglino et al, 2022), which may hinder their process of acculturation and result in a lower sense of belonging to the local community (Moscato et al, 2014). On the other hand, individuals migrated from countries that are more similar to Italy in terms of language and cultural values (such as Romanians) might assimilate more easily and even perceive themselves as being closer to natives than to citizens from other immigrant communities (Colombo, 2013; Musso et al, 2018).…”
Section: The Present Studymentioning
confidence: 99%
“…Indeed, the heterogeneous nature of the immigration phenomenon in Italy entails varied experiences of adjustment and integration across cultural communities. For instance, individuals who are characterized by distinct phenotypic traits (e.g., Chinese and African origins) or a larger cultural/religious distance from members of the mainstream society (e.g., Muslims) are at risk of being stigmatized and discriminated against (Ambrosini, 2013; Voglino et al, 2022), which may hinder their process of acculturation and result in a lower sense of belonging to the local community (Moscato et al, 2014). On the other hand, individuals migrated from countries that are more similar to Italy in terms of language and cultural values (such as Romanians) might assimilate more easily and even perceive themselves as being closer to natives than to citizens from other immigrant communities (Colombo, 2013; Musso et al, 2018).…”
Section: The Present Studymentioning
confidence: 99%
“…Among these post-migration stress factors, discrimination is one of the most burdening, significantly worsening the health and well-being of young people with migration background [5]. Research with adult as well as immigrant and refugee youth underscores the negative impact of discrimination on both physical (e.g., self-rated, hypertension, cardiovascular, respiratory) and mental health (affective disorders, e.g., anxiety, depression) [6][7][8]. A recent study among 1366 refugee and non-refugee migrant young people in five European countries revealed that perceived discrimination was associated with increased levels of mental health problems and lower overall well-being for refugees and nonrefugee migrants.…”
Section: Introductionmentioning
confidence: 99%
“…As the vocational school has been involved in the initiative “School without Racism, School with courage” [ 31 ] (an initiative of the association “Aktion Courage e.V.” and funded, among others, by the Federal Ministry for Family Affairs, Senior Citizens, Women and Youth for all school members to actively oppose discrimination, in the form of activities, such as discussions, theater performances, or exhibitions) for several years, the school was very interested in investigating the background of these results in more detail. Since previous studies have proven the strong link between discrimination and mental health issues [ 5 , 7 , 8 ], it was important from both the school and the scientific perspective, to understand which factors play a role in these high percentages. Also with regard to the integration of the currently arriving refugees from Ukraine [ 32 ], among them many children and adolescents, these aspects will again be of great importance.…”
Section: Introductionmentioning
confidence: 99%
“…The specific integration context that migrants face, increases their vulnerability and therefore, the broad range of social, economic, and integration challenges faced by these populations should be addressed (Priebe et al 2016). Unemployment, temporary residence status, and poor social integration are factors associated with increased mental health suffering among migrants (Giacco et al 2014;Voglino et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…While a wide range of evidence proves migrants are more vulnerable to mental health problems than non-migrants , Uphoff et al 2020, Voglino et al 2022, migrants are more reluctant to seek mental healthcare in conventional healthcare services (Boukpessi 2021;Kirmayer et al 2007;Knipscheer and Kleber 2008). This reluctance can be explained by a complex interplay of sociodemographic factors (e.g., gender, age, education), socio-economic factors (e.g., financial barriers, limited access to health insurance), structural and logistical factors (e.g., legal status defining healthcare access, language barriers, system of consultancy appointments) and sociocultural factors (Ahmadinia et al 2022;Anthony 2015;Kirmayer et al 2007;Scheppers et al 2006;Selkirk et al 2014).…”
Section: Introductionmentioning
confidence: 99%